The Chemical Evaluation of Natural Extracts of Marjoram Essential Oils as Antioxidants - Assad Abbas Khalaf (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Essential oils of Marjoram (Marjorana hortensis) has been evaluated for possible antioxidant activity. Essential oils were hydrodistilled and the chemical composition of volatile fraction was determined by GC. γ-Terpinene, sabinene, β-phellandrene, terpinen-4-ol and di (2-ethylhexyl) phthalate were the major constituents of Marjoram.  The reducing power of essential oils of Marjoram was measured by the ferricyanide method. Different concentrations of Marjoram oil (MO) 25, 50, 75, 100 and 200 ppm were investigated. Higher absorbance at 700 nm of the reaction mixture indicated greater reducing power. The reducing power of an antioxidant is an important parameter reflecting one aspect of its antioxidant properties. The obtained results revealed that increasing the antioxidant capacity is MO in all tested concentrations.   The antioxidant capacity of fat-soluble antioxidant was expressed as equivalents of α-tocopherol (nmol/g oil) using a molar absorption coefficient of α-tocopherol (є= 4.0 × 103 M-1 Cm-1. The percent of H2O2 scavenging activity of the tested EOs increased in the MO at all tested concentrations. There was a significant difference among all EOs samples in the percent of H2O2 scavenging activity. a positive correlation has been observed between concentrations and antioxidant activity for 3 days' test period. There were significant differences among the tested EOs in their antioxidant activities. For 3 days, the antioxidant activity of the tested EOs decreased statistically in MO. BHT on the peroxide value of sunflower oil as mmol eq O2/kgoil in the seventh day